Analisis Pendidikan Katekisasi dengan Pendekatan Total Quality Management dalam Meningkatkan Kualitas Pembinaan Warga - Hiara, Vini Irviana; Utubira, Everd Elseos Martin; Popoko, Yosis Karantina (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze catechism education and examine the implementation of the principle of Total Quality Management in improving the quality of faith formation. The method used is a qualitative descriptive method. The results of the study show that catechism education at GMIH is still understood reductively as an administrative requirement for sidi, not as a development of faith. In addition, the curriculum and teaching materials used are not yet relevant to the socio-cultural context and contemporary challenges of the congregation that have been formulated in the 33 Principles of Theology and Teachings of GMIH. From a quality management perspective, catechism education has not been focused on students, and decision-making has not been done based on data. Therefore, it is necessary to update the contextual catechization curriculum, revise teaching materials, and prepare technical instructions as a rail for the implementation of education.